Design of ultra-high strength, ultra-high ductility cementitious composites (UHS-UHDCC). (7th March 2022) - Lei, Dong-Yi; Li, Ming-Ang; Wang, Peng-Gang; Guo, Li-Ping; Li, Ying; Liu, Jia-Ping; Zhang, Peng; Li, Shao-Chun; Li, Chang-Cheng; Li, Zhi-Hong; Zeng, De-Zhao; Zhong, Bao-Min
Graphical abstract: Highlights: The realization of the pseudo strain hardening behavior needs to comprehensively tailor the interaction among fiber, mortar matrix, and fiber–matrix interface. For the fresh mortar matrix, an optimal range of viscosity can create a high fiber dispersion. To a certain degree, with the increasing of the fiber dispersion degree, the ductility increases. The proposed design framework for the PSH behavior is a very powerful tool for the mix design of UHS-UHDCC. Abstract: The realization of the pseudo strain hardening (PSH) behavior needs to comprehensively tailor the interaction among fiber, mortar matrix, and the interface. From the particle dense packing theory, using the river sands with the 240 μm-mean diameter and the 500 μm-maximum diameter as the fine aggregates, the high strength mortar matrix matching with PE fibers is designed, and the test for the bulk density of mortar matrix confirms the rationality of the analysis for the particle packing degree. For the fresh mortar matrix, an optimal range of viscosity can create a high fiber dispersion. In addition, there is a strong correlation (R 2 = 0.92) between the slump flow of mortar matrix and the viscosity, the slump flow can be as a simple way to test the rheology of mortar matrix. To a certain degree, increasing the fiber dispersion degree, the tensile ductility of UHS-UHDCC increases. Based on these observations, this study proposes a design framework for the PSH behavior of UHS-UHDCC, this design framework is a very powerful tool for the mix design of UHS-UHDCC.